Perennial plant patches are sinks for seeds in semi‐arid woodlands in varying condition. Issue 3 (13th March 2020) - Val, James; Travers, Samantha K.; Oliver, Ian; Eldridge, David J.
Abstract: Questions: Understanding the processes that influence resilience in semi‐arid woodland communities is of critical importance in landscapes where livestock grazing is the dominant land use and an important driver of site condition. Seed banks are a critical component of site resilience as their persistence can be crucial for recovering from disturbances. We predicted that site condition and landscape structural elements (perennial plant patches) would strongly influence the richness and density of the soil seed bank. Location: New South Wales, Australia. Methods: We conducted a seedling emergence study to investigate the germinable seed bank in semi‐arid woodland. Soil samples were collected from three woodland communities (Cypress pine, Black box, Red gum) from sites in three levels of site condition (poor, average, good) and from four patch types (tree, shrub, grass, open). Seed bank species were assigned to three plant trait groups based on: (a) origin; (b) lifespan; and (c) palatability. We used linear models to assess the effects of community, site condition and patch type on the richness and seed density of the germinable seed bank. Results: Site condition did not affect the seed bank density or richness, except for a lower density of highly palatable species at poor‐condition sites. Across all communities the importance of patch type on the soil seed bank density and richness varied with plant traits. The seed bank of perennial plant patches had a greater density of perennial species, a lower density of low palatability plants, and a greater richness of native and perennial species than interspaces. Conclusions: Our results demonstrate that the germinable soil seed bank in semi‐arid woodlands can be relatively resilient to degradation. This suggests that disturbed sites where perennial patches remain, may still have the ability to recover, because these patches act as important seed reservoirs. Abstract : Our study highlighted the importance of perennial plant patches across all communities and showed that seed bank density and richness varied with plant traits (origin, longevity and palatability). Our results demonstrate that the germinable soil seed bank in semi‐arid woodlands can be relatively resilient to degradation, when perennial patches are preserved, as these act as important seed reservoirs.